The Effect of Traditional Games Bebentengan on Aerobic Capacity and Agility - Ida Zubaida; Achmad Hufad; Aan Hendrayana; Suroso Mukti Leksono (JUARA : Jurnal Olahraga, 2021)
Some types of traditional games, such as bebentengan, have the same movements as some physical activities commonly carried out by individuals. Several studies on the effect of bebentengan on performance are still limited, so it is necessary to research the impact of bebentengan game treatment on aerobic capacity and agility. The research method used is an experimental method with one group pretest and posttest design without a control group, involving 20 teenagers from Serang City, Banten Province. The results showed that the bebetengan game treatment for three months increased the proportion of aerobic capacity by 5.27% and agility aspects by 3.28%. This study concludes that bebentengan games positively affect aerobic capacity and agility aspects in research subjects and can be used as an alternative to physical activity exercises.